A Reexamination of Corporate Governance and Equity Prices - Johnson, Shane A.; Moorman, Theodore C.; Sorescu, Sorin (Review of Financial Studies, 2009)
We reexamine long-term abnormal returns for portfolios sorted on governance characteristics. Firms with strong shareholder rights and firms with weak shareholder rights differ from the population of firms and from each other in how they cluster across industries. Using well-specified tests under this industry clustering, we find statistically zero long-term abnormal returns for portfolios sorted on governance. Our results have important implications for interpreting studies that link governance to firm value and stock returns, demonstrate the importance of the coarseness of industry definitions in financial research, and shed light on addressing statistical problems created by industry clustering in samples.